The first appearance of the zoonotic parasite Cryptosporidium mortiferum in human and tree and ground squirrels in Central Europe - Kváč, Martin; Konvalinová, Alena; Holubová, Nikola; Hůzová, Zuzana; Kicia, Marta; McEvoy, John; Beranová, Kristina; Sak, Bohumil (Emerging microbes & infections, 2025)
Cryptosporidium mortiferum, a parasite transmitted by squirrels, is beginning to spread in Europe. C. mortiferum was detected in a symptomatic human. A 44-year-old man from the Czech Republic suffered from gastroenteritis characterized by abdominal pain, nausea, and loose stools. Molecular analyses confirmed the XIVaA20G2T1 subtype in the patient's stool. At the same time, the same subtype of C. mortiferum was detected in three red squirrels and two ground squirrels in the area where the patient lived. The intensity of the infection was significantly higher in the red squirrels that died, while the ground squirrels showed no symptoms. The results of the study indicate that red squirrels and ground squirrels are the reservoirs for the infection.
Keywords: Feces; zdroje nemoci; gastroenteritida; Zoonoses; Cryptosporidium; Cryptosporidiosis; Česká republika; zoonózy; mužské pohlaví; Adult; Czech Republic; zvířata; feces; Humans; fylogeneze; Gastroenteritis; Sciuridae; Disease Reservoirs; dospělí; kryptosporidióza; Phylogeny; lidé; Male; Animals